DECISION SUPPORT SYSTEM SOCIAL MEDIA SELECTION IN PURCHAS-ING DECISIONS IN KOTIM USING TOPSIS METHOD - Eka Prasetyaningrum; Amelia Wulan Sari Sapitri; Selviana Yunita (STMIK Royal, 2024)
Abstract: Based on the era of globalization people in East Kotawaringin almost all people have used social media, for example, as a personal post some use it to see the promotion of beauty products fashion, and others. The KOTIM community has many who use social media, especially the Young Generation Z who have often used to buy products on social media, for example, Instagram, TikTok, and Facebook. This study will be made using the TOPSIS method for ranking to know which social media is often used by consumers. The researcher also made a questionnaire with Google form that will be tested for the validity or not of the data obtained using SPSS. The object of research is made in East Kotawaringin. The purpose of this study was to determine which social media is often used by the public to purchase decisions in the Kotim Regency. The result of the calculation using the TOPSIS method the social media platform with the highest rating is considered the best choice for decision-making, in this case, TikTok with a rating value of 1. It can be concluded that the social media platform that is widely used by KOTIM residents to make decisions is TikTok. Keywords: buying decision; social media; TOPSIS Abstract: Berdasarkan era globalisasi bahwa masyarakat di Kotawaringin Timur hampir seluruh masyarakat telah menggunakan media sosial, contohnya sebagai postingan pribadi ada juga yang menggunakan sebagai melihat promosi produk kecantikan dan fasion dan lainnya. Karena masyarakat KOTIM sudah banyak yang menggunakan media sosial apalagi para anak muda generasi z yang sudah sering menggunakan untuk membeli produk pada media sosial contohnya media sosial instagram, TikTok, dan juga facebook. Pada penelitian ini akan dibuat menggunakan metode TOPSIS untuk perangkingan agar mengetahui media sosial mana yang sering digunakan oleh konsumen. Peneliti juga membuat kuisoner dengan google form yang akan diuji valid atau tidak nya data yang didapat dengan menggunakan SPSS. Objek penelitian yang dibuat berada di Kotawaringin Timur. Tujuan dari penelitian ini adalah untuk mengetahui media sosial mana yang sering digunakan oleh masyarakat terhadap keputusan pemebelian pada wilayah kabupaten KOTIM. Hasil dari perhitungan menggunakan metode TOPSIS platform media sosial dengan peringkat tertinggi dianggap sebagai pilihan terbaik untuk pengambilan keputusan, dalam kasus ini adalah TikTok dengan peringkat nilai 1. Dapat disimpulkan bahwa platform media sosial yang banyak digunakan oleh penduduk KOTIM untuk mengambil keputusan adalah TikTok. Keywords: keputusan pembelian; media sosial; TOPSIS